2012
DOI: 10.1242/jcs.083279
|View full text |Cite
|
Sign up to set email alerts
|

Wiring through tunneling nanotubes – from electrical signals to organelle transfer

Abstract: Here we discuss these novel findings in the context of the two models that have been proposed for TNT formation, and focus on putative proteins that could represent TNT specific markers. We also shed some light on the molecular mechanisms used by TNTs to transfer cargos, as well as chemical and electrical signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
371
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 317 publications
(384 citation statements)
references
References 89 publications
12
371
1
Order By: Relevance
“…Although the mechanisms of their formation do appear to be different from filopodia, TNTs may however, arise from filopodialike structures. 9,21,22 We therefore addressed whether overexpression of PrP C also affected TNT formation, and performed similar TNTcounting and transfer experiments after overexpression of GFP-PrP C .…”
Section: Prp C Levels Affect Tnt Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms of their formation do appear to be different from filopodia, TNTs may however, arise from filopodialike structures. 9,21,22 We therefore addressed whether overexpression of PrP C also affected TNT formation, and performed similar TNTcounting and transfer experiments after overexpression of GFP-PrP C .…”
Section: Prp C Levels Affect Tnt Formationmentioning
confidence: 99%
“…5 TNTs are thin, actin-containing intercellular tubes, that may act as conduits that allow the passage of organelles, endocytic vesicles, protein aggregates and viruses between cells. 6,7,8,9 The mechanism by which PrP Sc transfers through TNTs has not been addressed. Because PrP is a GPI-anchored protein targeted to the outer leaflet of the plasma membrane we envision 2 possibilities by which PrP Sc could transfer though TNTs: by diffusion along the surface of the TNT, consistent with its localization to the plasma membrane or within the tube itself inside specific organelles or vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, several cell lines are reported to form TNTs express mutated or inactive p53. 2,3 Thus, substantial evidence suggests that p53 is not a master protein for TNT formation and further investigation is needed to dissect the molecular mechanisms underlying their formation.…”
Section: I) Statistical Analyses Revealed 12mentioning
confidence: 99%
“…The recent discovery that TNT-like structures exist in vivo suggests they may have an important role during tissue development and maintenance. 2,3 TNTs facilitate intercellular transfer of various cellular components and are thought to represent a novel form of cellular communication. [1][2][3] Recently, it was reported that TNT formation in primary rat hippocampal astrocytes and neurons was dependent on the activation of tumor suppressor protein p53 through cellular stress induction such as hydrogen peroxide (H 2 O 2 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation